THE CONNECTION BETWEEN EXERCISE AND THE WELL-BEING OF MIND AND BODY - Matmuratova Fauziya; Kenesbaev Asadbek; Aitbaeva Munira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This essay explores the connection between exercise and the well-being of the mind and body. It highlights the benefits of exercise for both physical and mental health, including weight management, disease prevention, stress reduction, improved cognitive function, and social interaction. The essay emphasizes the positive impact of exercise on overall well-being and encourages individuals to prioritize regular physical activity for optimal health.